CHALLENGES OF MODERN MARRIAGES - NON-PATRIMONIAL RIGHTS AND OBLIGATIONS OF SPOUSES - Nicoleta Roxana ŞERBĂNOIU (Challenges of the Knowledge Society)
The evolution of contemporary private law is due to the recognition of the importance of human rights, knowing a real progress lately, which has led to the protection of the person's subjective civil rights. It is very important that, in addition to legal coercive values, society should accept the importance of subjective rights and respect them. In terms of family law, the personal obligations of spouses are important. In order to be effective, these rights must be applied carefuly and it is necessary that they come to defend a person both physically and mentally. It is very important that, in addition to legal coercive values, society should accept the importance of civil subjective rights and respect them. Although at European level we can observe an exponential increase of the values protected due to European Convention on Human Rights and its implementation, in Romania the respect of the civil subjective rights remains at the discretion of individuals, force can not cover all the cases that may arise. Civil subjective rights and obligations, in terms of family law, are impotant, especialy the personal obligations of spouses. Personal rights and obligations are inseparable from spouses and can not be alienated. They can not be the subject of the matrimonial agreement or of any other contracts. This provides an essential principle of family law - the equality of spouses in family – that is based on the Universal Declaration of Human Rights, the Convention on the Political Rights of Women, the Convention on the Elimination of All Forms of Discrimination against Women, Civil Code.